Ethics in social research - Love, Kevin (Studies in qualitative methodology ;, 2012)
Recent shifts in the economic, cultural and theoretical context within which Higher Education institutions organise and pursue research activities, alongside other factors has prompted a reconsideration of the role of social research - its purpose, its practice and its ethical alignments. Blending practice-based reflection with philosophically informed theoretical work, this volume brings together a field of leading and rising academics from sociology and social theory to consider - for the first time in a published collection - both contemporary ethical issues in social research, and the increasing impact of ethics on social research. Situated at the intersection of ethics and knowledge production, these essays elaborate key ethical themes, trace the concrete negotiations of 'live' ethical issues in empirical qualitative research, and intensify the ethical encounter with innovative perspectives drawn from recent developments in philosophy and social theory. This collection is both informative and provocative, supporting the ethical negotiations of empirical researchers and enhancing understanding of the complex imbrication of ethics and knowledge in contemporary social research.